Exploration on High School Students’ Grit: Its Effects on the Students’ Potential Development - Yudiar, Ahmad; Yudha, Eka Sakti; Sartono, Sartono (Jurnal Kajian Bimbingan dan Konseling, 2021)
The education process in Indonesia has been implemented using a variety of modern tools, but it should be understood that the quality of learning activities in the classroom is also influenced by the interactions that occur in the classroom. Teachers must understand that to create interaction in the classroom, they must first understand the grit level that can help make learning fun. The purpose of this study was to determine the grit level of high school students in Bangka Belitung Province, Indonesia. This research is survey research conducted in Bangka Belitung Province and involves 770 respondents. The results showed that (1) 25 percent of respondents were distracted by a new idea or activity, (2) 47 percent of respondents who did not give up in achieving their goals even though they experienced failure, (3) 23 percent of respondents did not pursue other goals after setting goals, (4) 39 percent of respondents are persistent in their business or work, (5) 25 percent of respondents cannot maintain their focus when carrying out long activities, (6) 46 percent of respondents always try to complete each of their activities, (7) 35 percent of respondents have interests that change every year, (8) 32 percent of respondents is diligent and do not give up easily, (9) 23 percent of respondents were obsessed with activity but it did not last long, (10) 41 percent of respondents have experienced failure in conquering important challenges.